2013
DOI: 10.1002/bab.1082
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced stability of newly isolated trimeric l‐methionine‐N‐carbamoylase from Brevibacillus reuszeri HSN1 by covalent immobilization

Abstract: Newly isolated and partially purified trimeric l-methionine-N-carbamoylase from Brevibacillus reuszeri HSN1 was immobilized by covalent coupling to a well-known support material, Eupergit® C. Approximately 80% enzyme activity yield was achieved with ≈61% binding of a soluble protein from a solution containing 5 mg/mL protein. The immobilized preparation was found to be quite unstable due to a poor multisubunit covalent interaction of trimeric enzyme. Additional cross-linking with polyaldehyde-dextran was done … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
(118 reference statements)
1
2
0
Order By: Relevance
“…Similar results were obtained when Deinococcus radiodurans NSAAR (DraNSAAR) was immobilized, resulting in a 90% decrease of its specific activity (Yen et al, 2010). Regarding L-carbamoylases, previous studies have shown that immobilization of the enzymes from Arthrobacer and Bacillus genera has resulted in a substantial decrease in their specific activity (Ragnitz et al 2001a and b;Yen et al, 2010;Nandanwar et al 2013), except in the case of a recombinant (Asp) 6tagged L-carbamoylase from Arthrobacter (AauBLcar), which maintained similar activities to the enzyme in solution (Ragnitz et al 2001 enzandmicrobtech). BsLcar could also be reused for several cycles as other Bacillus L-carbamoylases, maintaining similar significant half-lifes (Nandawar et al 2013;Yen et al 2010).…”
Section: Discussionsupporting
confidence: 64%
“…Similar results were obtained when Deinococcus radiodurans NSAAR (DraNSAAR) was immobilized, resulting in a 90% decrease of its specific activity (Yen et al, 2010). Regarding L-carbamoylases, previous studies have shown that immobilization of the enzymes from Arthrobacer and Bacillus genera has resulted in a substantial decrease in their specific activity (Ragnitz et al 2001a and b;Yen et al, 2010;Nandanwar et al 2013), except in the case of a recombinant (Asp) 6tagged L-carbamoylase from Arthrobacter (AauBLcar), which maintained similar activities to the enzyme in solution (Ragnitz et al 2001 enzandmicrobtech). BsLcar could also be reused for several cycles as other Bacillus L-carbamoylases, maintaining similar significant half-lifes (Nandawar et al 2013;Yen et al 2010).…”
Section: Discussionsupporting
confidence: 64%
“…Due to their thermal instability as well as oxidative and proteolytic sensitivity many efforts have been made for the immobilization of hydantoinases and carbamoylases with visible success (Pietzsch et al 1998; Ragnitz et al 2001b; Chiang et al 2008; Nandanwar et al 2013). Most investigations are dealing with encapsulation, covalent immobilization or non-covalent adsorption techniques.…”
Section: Discussionmentioning
confidence: 99%
“…Up to now, very little research has been done on this spore-forming species. The only functional gene from B. reuszeri is l -methionine- N -carbamoylase, which will be a potential biocatalyst for the production of l -α-amino acids ( 3 , 4 ). Given its taxonomic history and no available genomic information of B. reuszeri , its type strain NRRL NRS-1206 T was selected as one of the research objects in our genome sequencing project for genomic taxonomy and phylogenomics of Bacillus -like bacteria.…”
Section: Genome Announcementmentioning
confidence: 99%